Grounds for Refusal of Green Trademark Under the EU Legal Framework and Suggestions for Vietnam - Thuy, Pham Ngoc (VNU Journal of Science: Legal Studies; Article in pressDO - 10.25073/2588-1167/vnuls.4745, 2026)
Environmental pollution is one of the most serious problems facing mankind today, which forces businesses to make commitments to both environmental and economic sustainability in their marketing campaigns and products. To attract environmentally conscious customers and creat a differentiation between normal and sustainable products in the market, businesses have been using green trademarks for their goods and services. The current EU legislation on trademarks has regulated the absolute grounds to deny green trademark registration. This article will analyze these regulations and make proposals to strengthen the provision of the Vietnam Intellectual Property Law.